Synthesis of (R)- and (S)-2-N-methylamino-2,3-dimethylbutanamides and (R)- and (S)-(5-isopropyl-1,5-dimethyl-4,5-dihydro-1H-imidazol-4-on-2-yl)pyridines - Drabina, Pavel; Sedlák, Miloš; Růžička, Aleš; Malkov, Andrei V.; Kočovský, Pavel (Elsevier, 2008)
Both (R)- and (S)-2-N-methylamino-2,3-dimethylbutanamides have been prepared by the reductive benzylation of (R)- and (S)-2-amino-2,3-dimethylbutanamides, followed by reductive methylation and hydrogenolytic removal of the benzyl group. The reductive benzylation is chemoselective, and not accompanied by dibenzylation even with the application of excess benzaldehyde. Acylation of the (R)- and (S)-2-N-methylamino-2,3-dimethylbutanamides with picolinic acid and subsequent ring closure gave the respective (R)- and (S)-(5-isopropyl-1,5-dimethyl-4,5-dihydro-1H-imidazol-4-on-2-yl)pyridines. Their complexes with Cu(I) catalyze the Kharash–Sosnovsky allylic oxidation with overall yields as high as 99% but with low enantioselectivity.